Laboratory evaluation of higher-order aberrations and light scattering in explanted opacified intraocular lenses - Łabuz, Grzegorz; Yildirim, Timur Mert; Auffarth, Gerd U.; Son, Hyeck Soo; Khoramnia, Ramin (Eye and Vision, 2021)
Intraocular lens (IOL) calcification is a serious condition that can only be treated by removing the clouded lens. Since explantation bears the risk of complications, it is often deferred until the patient finds the symptoms intolerable. Usually, as the IOL opacifies, visual acuity is minimally affected early on. In this study, we assessed the impact of IOL opacification on optical quality.